The Social Dimension of Teacher Student Interaction in English Teaching - Zahara Safrina Aini Lubis; Hasibuan, Ahmad Laut; Asnawi; Didik Santoso (PT Inovasi Pratama Internasional, 2026)
This qualitative research investigates the social dimensions, power relations, and underlying ideologies in teacher-student interaction within the English classroom at MTS PP Al-Qomariyah. Despite the curriculum shift toward a student-centered approach, there is a potential for unintentional power imbalances and ideological influences that limit student exploration. This study aims to identify the social dimensions (social norms, status, roles, and power) and understand the influence of underlying learning ideologies. The research employed a Critical Discourse Analysis (CDA) methodology, utilizing Norman Fairclough’s three-dimensional framework. Participants were the English teacher and Grade IX students at the school. Data were collected through classroom observation and analysis of interaction transcripts, with analysis focused on connecting discourse to ideology and social practice. The findings reveal that the classroom interaction is primarily shaped by an Asymmetrical Hierarchy rooted in the Pesantren (Islamic boarding school) context. This hierarchy is constantly reinforced by Hegemonic Values such as Adab (etiquette) and Kepatuhan (obedience), which manifest linguistically through formal address. Furthermore, the underlying ideology is dual: Instrumental (English as a technical tool) and Normative (requiring content to be filtered by religious/cultural values). In conclusion, the traditional institutional context strongly impacts modern pedagogical roles. The study recommends implementing practical strategies to democratize classroom discourse and foster a more empowering, inclusive learning environment